Politik Simulacra dalam Ekstasi Media Sosial di Indonesia - Novi Indah Sari (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2020)
Jean Baudrillard through Simulation (1983) made a thoughtful approach that predicted that reality would eventually die. The 'new world' which Baudrillard calls the 'Simulacra Galaxy', has in fact engulfed all aspects of life, including democracy. Dialectics on democracy, which provides an opportunity for every child of the nation to freely express opinions, actually leads to freedom that crosses the boundaries of the human rights of fellow citizens of the nation. Quietly, primordialism of religion, class, ethnicity, regionalism, and all exclusive social groupings has risen again, which is compounded with the liberal political process which since the reformation has been transformed into new shackles that limit national life. Regional autonomy which is increasingly liberal with the aroma of federation has strengthened the barriers of the new primordial revitalism. The predictions of the threat of "independence" and "referendum" which erupted in one or two regions when the 2019 election process tended to harden, shows how short the reasoning of some of the nation's children in this country is.